The role of TiO2 nanotube surface on osseointegration of titanium implants: Biomechanical and histological study in rats - Alves-Rezende, Maria C. R. [UNESP]; Capalbo, Letícia C. [UNESP]; De Oliveira Limírio, João P. J. [UNESP]; Capalbo, Bruna C. [UNESP]; Limírio, Pedro H. J. O.; Rosa, Jorge L. (Wiley, 2020)
The nanoscale surface of titanium has been studied to improve the cellular recognition of the biological microenvironment and to increase bone–implant interaction. The aim of this study was to analyze the effect of a titanium oxide (TiO2) nanotube surface with a machined surface on osseointegration tibia implants without primary stability. This study used an experimental design, divided into two groups (n = 16): commercially pure titanium machined implants (Cp-Ti Ma) and commercially pure titanium anodized implants (Cp-Ti An). Titanium nanotubes were produced by anodic oxidation, and the topography of surface was analyzed using field emission scanning microscope (FE-SEM). The implants (2.1 × 2.8 mm Ø) were surgically placed in the right tibia (defects with milling drill 2.5 × 3.2 mm Ø) of 32 Wistar male rats (250–300 g). The animals were euthanized at 7 weeks postoperatively. The maximum value of removal torque was measured (N/cm) in the right tibia half of each group (8 animals/8 tibiae); the other half of each group underwent a nondecalcified protocol, stained with Stevenel blue/Alizarin red, and the formation of bone tissue in close contact to the implant was measured. The obtained data were analyzed statistically (t test). Differences were considered statistically significant for α < 0.05. Cp-Ti An implants were significantly higher in removal torque and peri-implant bone healing compared with Cp-Ti Ma implants (p <.01). Within the limitations of this study, it was observed that the surface modification of titanium by anodization (TiO2 nanotubes) can improve osseointegration, and this may be very useful to reduce the time required for peri-implant bone formation.
Keywords: dental implants; nanotubes; osseointegration; titanium